Regular expression pocket reference - Stubblebine, Tony (O'Reilly, 2007)
"Regular expressions arc a language used for parsing and manipulating text. They are often used to perform complex search-and-replace operations, and to validate that text data is well-formed." "Today, regular expressions are included in most programming languages, as well as in many scripting languages, editors, applications, databases, and command-line tools. This book aims to give quick access to the syntax and pattern-marching operations of the most popular of these languages so that you can apply your regular-expression knowledge in any environment."--Jacket